L. N. Gumilev as a representative of Russian cosmism - Karako, Petr S. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
The article reveals the features of the concept of ethnogenesis of L. N. Gumilev, its justified and controversial aspects. Considerable attention is paid to revealing the role of biosphere and space ideas of V. I. Vernadsky on the formation and expression of L. N. Gumilev’s cosmic views. Their basis was the idea of cosmic conditioning of the change of ethnic groups in the real history of mankind. He made an attempt to uncover the connection between history of people and history of nature. His concern is emphasized by the nature of man’s attitude to nature, the importance of affirming reasonable forms of people’s attitude to it. It is concluded that L. N. Gumilev was involved in the number of representatives of Russian cosmism.